The IJMS World Conference of Medical Student Research and an Overview of the IJMS Volume 10 Issue 2 - Adnan Mujanovic; Vincent Kipkorir; Cesare Mercalli; Arkadeep Dhali; Purva Shah; Camila Velandia; Ciara Egan; Mihnea-Alexandru Găman; Juan C. Puyana; Francisco J. Bonilla-Escobar (University Library System, University of Pittsburgh, 2022)
We introduce the first IJMS World Conference of Medical Student Research as a unique opportunity for medical students and early-career scientists around the globe to share the results of their research in an online worldwide platform, aimed at increasing accessibility to research for medical students and creating bonds of collaborations between participants and future scientists and leaders of medical research education. This is also the second issue of the 10-year anniversary of the Journal, and we describe in summary the published research and experiences of this issue.